ANALISIS SINEMATIK DAN NARASI VISUAL FILM ANIMASI “RAYA AND THE LAST DRAGON” - Iwan Iwan Muhammad Ridwan (JURNAL Dasarrupa: Desain dan Seni Rupa, 2023)
Raya and the Last Dragon is an animated film produced by Walt Disney Animation Studios with the storyline of Raya's adventures as the main character in an imaginary country called Kumandra. This animated film has a cultural style and local identity that is identical to Southeast Asian culture, including Indonesian culture. It is these cultural identities and symbols that encourage this research. Through a descriptive analysis method, the meaning of symbols or cultural identities contained in the visual and cinematic narratives of the animated film Raya and the Last Dragon will be explained based on studies using Roland Barthes' semiotic theory. The results obtained from the analysis using two stages of significance, namely the first level of denotational meaning and the second level of connotative meaning, are the messages contained in several excerpts in each scene of the animated film which show the meaning of Southeast Asian cultural symbols, as well as what is visible from the behavior of each character, as well as the visual and cinematic narrative that greatly influences the animated film.